Making Implementation Science More Rapid: Use of the RE-AIM Framework for Mid-Course Adaptations Across Five Health Services Research Projects in the Veterans Health Administration - Glasgow, Russell E.; Battaglia, Catherine; McCreight, Marina; Ayele, Roman Aydiko; Rabin, Borsika Adrienn (Frontiers in Public Health, 2020)
Introduction.Implementation science frameworks have helped advance translation of research to practice. They have been widely used for planning and post-hoc evaluation, but seldom to inform and guide mid-course adjustments to intervention and implementation strategies. Materials and Methods.This study developed an innovative methodology using the RE-AIM framework and related tools to guide mid-course assessments and adaptations across five diverse health services improvement projects in the Veterans Health Administration (VA). Using a semi-structured guide, project team members were asked to assess the importance of and progress on each RE-AIM dimension (i.e., reach, effectiveness, adoption, implementation, maintenance) at the current phase of their project. Based on these ratings, each team identified one or two RE-AIM dimensions for focused attention. Teams developed proximal goals and implementation strategies to improve progress on their selected dimension(s). A follow-up meeting with each team occurred approximately 6 weeks after the goal setting meeting to evaluate the usefulness of the iterative process. Results were evaluated using both descriptive quantitative analyses and qualitative assessments from interviews and meeting notes. Results. A median of seven team members participated in the two meetings. Qualitative and descriptive data revealed that the process was feasible, understandable and useful to teams in adjusting their interventions and implementation strategies. The RE-AIM dimensions identified as most important were adoption and effectiveness, and the dimension that had the largest gap between importance and rated progress was reach. The dimensions most frequently selected for improvement were reach and adoption. Examples of action plans were summarizing stakeholder interviews for leadership, revising exclusion criteria, and conducting in-service trainings. Follow-up meetings indicated that teams found the process very useful and were able to implement the action plans they set. Discussion. The iterative use of RE-AIM to support adjustments during project implementation proved feasible and useful across diverse projects in the VA setting. Future research should replicate these findings and further develop the methodology, as well as explore the optimal frequency and timing for these iterative applications of RE-AIM. More generally, greater focus on more rapid and iterative use of implementation science frameworks is encouraged to facilitate successful translation of research to practice.